Insurance companies’ lack of LGBTQ+ affirmation: discrimination, distrust, and dissatisfaction among LGBTQ+ people - Nowaskie, Dustin Z.; Blackwood, Dehandra; Garcia, Frank; Flautero, Jorge D. (Frontiers in Sociology, 2025)
IntroductionLGBTQ+ individuals have historically faced and continue to experience stigma and discrimination in various areas, including healthcare. There is very limited data regarding LGBTQ+ people’s perceptions of their health insurer and health insurer workers.MethodsAn online cross-sectional survey was conducted with a national sample of United States residents, who responded to questions about their healthcare, including experiences with their health insurer and health insurer workers.ResultsCompared to cisgender, heterosexual people (n = 1,400), LGBTQ+ people (n = 1,234) reported significantly poorer experiences with their health insurer, including being dissatisfied with their health insurer; believing their health insurer is not their advocate; distrusting their health insurer; not knowing what is covered in their health plan; being dissatisfied with providers in their health plan; and not believing their health insurer meets their needs. Additionally, compared to cisgender, heterosexual people, LGBTQ+ people conveyed poorer experiences with health insurer workers, including health insurer workers not addressing them by their names; not being comfortable when interacting with them; not being coordinated; misgendering them; and being discriminatory toward them.DiscussionLGBTQ+ communities continue to face significant healthcare disparities, including stigma and discrimination from health insurers and health insurer workers. Longitudinal dedication to LGBTQ+ education, advocacy, and institutional reform is necessary to dismantle the entrenched discrimination in health insurer environments and create more equitable, supportive environments for all LGBTQ+ people.